2018
DOI: 10.1590/1678-4685-gmb-2017-0098
|View full text |Cite
|
Sign up to set email alerts
|

The genomes of three Bradyrhizobium sp. isolated from root nodules of Lupinus albescens grown in extremely poor soils display important genes for resistance to environmental stress

Abstract: Lupinus albescens is a resistant cover plant that establishes symbiotic relationships with bacteria belonging to the Bradyrhizobium genus. This symbiosis helps the development of these plants in adverse environmental conditions, such as the ones found in arenized areas of Southern Brazil. This work studied three Bradyrhizobium sp. (AS23, NAS80 and NAS96) isolated from L. albescens plants that grow in extremely poor soils (arenized areas and adjacent grasslands). The genomes of these three strains were sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…could be mapped during the sequencing, it must be taken into account that Bradyrhizobia can also be hosted by other legumes, such as lupines. There is evidence of this in Brazil [24], USA [25], and Spain and Chile [26], where Bradyrhizobia was isolated from different lupine species. For the field control (C BW) and the other samples from the Pillnitz experimental station, however, this can be ruled out, as no cultivation with lupines has yet taken place on this site.…”
Section: Presence Of Rhizobia In Soilmentioning
confidence: 97%
“…could be mapped during the sequencing, it must be taken into account that Bradyrhizobia can also be hosted by other legumes, such as lupines. There is evidence of this in Brazil [24], USA [25], and Spain and Chile [26], where Bradyrhizobia was isolated from different lupine species. For the field control (C BW) and the other samples from the Pillnitz experimental station, however, this can be ruled out, as no cultivation with lupines has yet taken place on this site.…”
Section: Presence Of Rhizobia In Soilmentioning
confidence: 97%
“…Several works have reported that these microsymbionts have a key role in the adaptation of legumes to soils poor in nitrogen and with high contents of metals and As (Fagorzi et al, 2018). For example, species from the genus Bradyrhizobium are found associated with the legume Glycine max growing in soils with a high content of As, and with the legume Lupinus luteus in soils with high concentrations of Cu, Cd and Pb (Fagorzi et al, 2018;Granada et al, 2018). The great abundance of Bradyrhizobium in the soil samples of our study may be related to the presence of Retama sphaerocarpa, a leguminous plant observed across the three sampling areas (A, B and C).…”
Section: Structure Of the Microbial Communitymentioning
confidence: 99%